PERBEDAAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA BELAJAR DENGAN PEMBELAJARAN KONTEKSTUAL DAN PEMBELAJARAN KONVENSIONAL DI KELAS X SMA N 1 B.PURBAPADA MATERI STATISTIKA T.A 2017/2018 - SARI MUTHIA SILALAHI (LP2MTBM MAKARIOZ, 2019)
This study aims to determine the description of students' mathematical communication skills by applying 2 learning strategies, namely contextual learning strategies and conventional learning in class X SMA N 1 B. Purba T.A. 2017/2018 and the process of answering mathematical communication skills of students who learn with contextual learning are better than conventional learning. This research is a quasi-experimental research. The population in this study were all grade X students of SMA N 1 B. Purba T.A. 2017/2018 which consists of 4 parallel classes. Meanwhile, the sample in this study is a homogeneous sample, randomly selected after being given a pretest for the population, students as a sample of 2 classes, namely class X-2 (experimental class) of 30 people and class X-1 (control class) as many as 30 people. From the calculation results obtained = 2.079 and = 2,000 with = 58 and the real level α = 0.05. It can be seen that, it is rejected or accepted. So from the results of research and hypothesis testing concluded that the mathematical communication skills of students who learn with contextual learning strategies are higher than students who learn with conventional learning on statistical material in SMA N 1 B.Purba. Based on the student answer process, classes that follow contextual learning strategies are better than students who follow conventional learning.